Diseño de un sistema de procedimientos administrativos, financieros y contables, para el cumplimiento de las obligaciones tributarias en las actividades de importación y exportación de mercaderías en el Ecuador - Llumipanta Castro, Claudia Gabriela (2013)
This degree work presents an administrative, financial and accounting analysis for the tax obligations compliance on import and export of merchandise in Ecuador. Exports are defined as merchandise outlet from Ecuador to foreign countries, they are the main item that cause income dollars from foreign. Imports are explained as merchandise entrance from foreign to Ecuador, they are means foreign exchange outlet. For a company or individual can execute external trade, they have to acquainted with the SENAE and its functions, as well as the different customs regime and trading policies in order to choose the best decision according to the needs.